Sanksi Pidana Terhadap Pelaku Pemotong Dana Bantuan Sosial Covid - 19 - Kadek Agus Indra Ana Putra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
The criminal act of embezzlement and fraud committed by deducting the Covid-19 social assistance funds, specifically the provisions in article 372 of the Criminal Code. Meanwhile, fraud is regulated in Article 378 of the Criminal Code. This research focuses on criminal or legal sanctions against the perpetrators of cutting Covid-19 social assistance funds based on the law, namely the Criminal Procedure Code (KUHP). The purpose of this research is to regulate legal sanctions against perpetrators of Covid-19 social assistance fund cutters. It applies the normative legal method by using a conceptual and a case approach.. The sources of legal materials used are primary, secondary and tertiary sources of law. The technique of collecting legal materials is done by recording, quoting, reading, and summarizing the literature related to the formulation of the problem which is then analyzed systematically. The result of the research shows that the criminal sanctions against the perpetrators of cutting Covid-19 social assistance funds based on the Criminal Procedure Code (KUHP), are regulated in article 372 of the Criminal Code for embezzlement, while fraud is subject to article 378 of the Criminal Code. The perpetrator was charged in accordance with Article 372 regarding embezzlement and Article 378 of the Criminal Code regarding the criminal act of fraud.